AB0109 The Lung Microbiome in Rheumatoid Arthritis and Associated Local/systemic Autoimmunity. (15th July 2016) - Scher, J.U.; Joshua, V.; Ubeda, C.; Artacho, A.; Grunewald, J.; Segal, L.; Catrina, A.I.
Abstract : Background: Airway abnormalities and increased lung tissue citrullination is found in both RA patients and individuals at at-risk for the development of disease. Recent data suggest that the gut ( Prevotella copri ) and oral ( Porphyromonas gingivalis ) microbiome might potentially contribute to the priming of an aberrant systemic immune response characteristic of RA. Objectives: Our objective was to study whether RA lung microbiome contains distinct taxonomic features associated with local and/or systemic autoimmunity. Methods: Bronchoalveolar lavage (BAL) samples from 20 subjects with RA, 10 with sarcoidosis and 28 healthy controls were obtained by research bronchoscopy. 16S rRNA sequencing was performed to define microbiota composition. Autoantibodies, including anti-CCP, RF and ACPAs were also measured in sera of RA subjects. Results: The 16s sequencing data showed similar alpha/beta diversity between RA and sarcoid groups, but significantly different from healthy (ANOSIM test; p=0.002 and 0.021 for healthy vs RA and healthy vs sarcoid, respectively). Taxonomic comparison between groups was performed using LEfSe, which revealed several significant differences. RA BALF samples had a decrease in the families Actinomycetaceae ( P<0.0001 ) and Spirochaetaceae ( P=0.0009) compared to healthy. Burkholderia was significantly decreased in both RA and sarcoidosis compared to controls. The genus Treponema (also highly associated with periodontitis) was exclusively found in healthy subjects' BALF (P<0.01 vs RA). RA disease activity was positively correlated with Micrococcus and Renibaterium at the genus level, and with various OTUs belonging to Pseudonocardia and Xanthomonadaceae whereas, the genus Veillonella and unclassified Oxalobacteraceae had a negative correlation. Levels of local autoantibodies i.e., anti-CCP2 correlated positively with the genus Corynebacterium, Megasphera and unclassified Comamonadaceae . Circulating anti-CCP (IgA isotype), had a positive significant correlation with relative abundance of BALF Enhydrobacter and unclassified Bradyrhizobiaceae (P=0.015 and 0.004, respectively). A modest association with erosive disease was observed with the presence and abundance of Pseudonocardia in the RA BALF (85% of erosive RA patients vs. 23% of non-erosive RA; P=0.019). Conclusions: Despite the relatively small number of samples analyzed, several taxonomic differences were noted between groups. Correlations between relative abundance of specific taxa in RA BAL with serum autoantibodies (i.e., anti-CCP) support an association between the lung microbiome and the host immune phenotype in RA. Further evaluation of the functional aspects of this microbiome may provide insights into its possible contribution to RA. Disclosure of Interest: None declared